2022
DOI: 10.26719/emhj.22.071
|View full text |Cite
|
Sign up to set email alerts
|

15-year evaluation of changes in the HBsAg positivity rate in pregnant women in Turkey: the prominent effect of national vaccination

Abstract: Background: The detection of hepatitis B surface antigen (HBsAg) positivity in pregnant women before delivery is crucial to preventing mother-to-child transmission of hepatitis B virus. Aim: This study aimed to evaluate the status and rate of testing for HBsAg, the rate of HBsAg positivity and the distribution of this rate by age and to evaluate changes in the HBsAg positivity rate in pregnant women over the study period. Methods: We conducted a multicentre, cross-sectional, descriptive study covering the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In Turkey, approximately 3.3 million people (4.57% of the population) are considered HBsAg (hepatitis B surface antigen) positive ( 2 ). A study published by Tosun et al has recently reported HBsAg positivity of 1.1% from 22 provinces and seven regions of Turkey ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Turkey, approximately 3.3 million people (4.57% of the population) are considered HBsAg (hepatitis B surface antigen) positive ( 2 ). A study published by Tosun et al has recently reported HBsAg positivity of 1.1% from 22 provinces and seven regions of Turkey ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Three studies published between 2013-2022 have shown HBsAg positivity rates of 3.5%, 1.1%, and 0.3% among people born in 1998 and after in Turkey, respectively ( 3 , 12 , 13 ). Although it has been nearly three decades since the HBV vaccine was included in the national vaccine program, the number of comprehensive studies related to seroprevalence in the population, including adults and the pediatric population, is low in our country.…”
Section: Introductionmentioning
confidence: 99%